More to Pan than Just Panorama and Ramajay - Cuffy, David (Trinidad Guardian)
The article laments that steelband only receives public attention and scrutiny for the duration of a particular national competition, Panorama. After Panorama, the steelband does not attract the kind of public support that it deserves and which it is entitled as being the national musical instrument. There are calls to break with tradition and give full, year-round support to the steelband and the efforts of its exponents.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Popular music -- Social aspects -- Trinidad and Tobago; Steel drum (Musical instrument) -- Trinidad and Tobago